Folliculosebaceous neoplasms: A review of clinical and histological features. Issue 3 (March 2017) - Ho, Jonathan; Bhawan, Jag
Abstract: Numerous benign and occasionally malignant tumors arise from the folliculosebaceous apparatus. Confusing terminology, rarity of malignant variants and overlapping histological features can lead to diagnostic uncertainty. This review highlights the clinical and histopathological features that help to classify these entities, as well as the various syndromes associated with certain members of this large family of tumors.